The Use of Educational Media in Introducing Asmaul Husna to Early Childhood: A Literature Review - Fauzeh Fauzeh; Terza T ravelancya D.P; Ivonne Hafidhatil Kiromi (Journal of Childhood Development, 2024)
This study explores using educational media to introduce Asmaul Husna in Early Childhood Education at Anggrek Dawuhan Kindergarten, Krejengan Probolinggo. The research data was collected through a literature review method, where the researcher gathered information from various sources, including books, undergraduate theses, master's theses, journals, and articles from official websites that have been indexed and accredited over the past five years. The foundation of early childhood education should encompass the philosophical and religious values upheld by the child's surrounding environment and religion. Religious education in this context emphasizes understanding religion and its application in daily actions. Religion is also fundamental for instilling faith in children, beginning with teaching faith in Allah SWT. Asmaul Husna is one way to teach children the value of faith. Given that children might perceive religious values as abstract, teachers need to use various educational media as tools to introduce Asmaul Husna to them. The research results indicate that diverse educational media are developed to assist children in learning about Asmaul Husna.